A photoelectrochemical aptasensor based on double Z-scheme α-Fe2O3/MoS2/Bi2S3 ternary heterojunction for sensitive detection of circulating tumor cells - Feng, Kai; Di, Ya; Han, Meng; Yan, Weitao; Guo, Yulin; Huai, Xiangqian; Wang, Yimin (Frontiers in Bioengineering and Biotechnology, 2024)
A novel photoelectrochemical (PEC) aptasensor based on a dual Z-scheme α-Fe2O3/MoS2/Bi2S3 ternary heterojunction for the ultrasensitive detection of circulating tumor cells (CTCs) was developed. The α-Fe2O3/MoS2/Bi2S3 nanocomposite was prepared via a step-by-step route, and the photoproduced electron/hole transfer path was speculated by conducting trapping experiments of reactive species. α-Fe2O3/MoS2/Bi2S3-modified electrodes exhibited greatly enhanced photocurrent under visible light due to the double Z-scheme charge transfer process, which met the requirement of the PEC sensor for detecting larger targets. After the aptamer was conjugated on the photoelectrode through chitosan (CS) and glutaraldehyde (GA), when MCF-7 cells were presented and captured, the photocurrent of the PEC biosensing system decreased due to steric hindrance. The current intensity had a linear relationship with the logarithm of MCF-7 cell concentration ranging from 10 to 1×105 cells mL−1, with a low detection limit of 3 cell mL−1 (S/N = 3). The dual Z-scheme α-Fe2O3/MoS2/Bi2S3 ternary heterojunction-modified PEC aptasensor exhibited high sensitivity and excellent specificity and stability. Additionally, MCF-7 cells in human serum were determined by this PEC aptasensor, exhibiting great potential as a promising tool for clinical detection.